Muslim educators in American communities - Glenn, Charles Leslie, 1938- (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"Political rhetoric and popular concern about the presence in the United States of immigrants from predominantly-Muslim societies has remained largely detached from the actual reality of the lives and contributions of these immigrants and their children. The studies presented here seek to correct this ignorant reaction by presenting objective information from schools that such immigrants have created and sustained. The first looked at seven explicitly-Islamic secondary schools, focusing on the formation of character and American citizenship, while the other studied public charter schools established by immigrants from Turkey, focusing on academic results"--